The Extent of Applying the International Accounting Education Standard for Technical Competence in Accounting Programs at King Khalid University in the Kingdom of Saudi Arabia: A Case Study - Mona Abdelrhman Yagoub (University of Science and Technology, Yemen, 2021)
The study aimed to identify the extent of applying the international accounting education standard for the technical competence in accounting programs at King Khalid University in the Kingdom of Saudi Arabia. The study followed the quantitative approach using the descriptive and inferential analysis method to test the hypotheses and achieve the study objectives. The study population was all faculty members of the accounting programs (diploma and bachelor) at King Khalid University, which has a total number of (64) members, from which a sample of 45 (75%) participants was randomly selected. Major findings revealed that the application of learning areas and outcomes related to technical competence specified in the International Accounting Education Standard (IES2) enabled graduates of accounting programs to possess the necessary skills to find solutions to complex accounting problems, which would lead to the required technical competence levels by completing the specified accounting program. It was also found out that areas and learning outcomes of technical competence were applied in accounting programs at King Khalid University. Based on these results, the study stressed the need for more studies on the scope of applying the International Accounting Education Standard (IES2) in accounting programs at universities in various countries due to its significant contribution to program development and the competence of technical graduates. The accounting programs at King University Khaled should also pay more attention to some areas of technical competence and related learning outcomes that have achieved lower rates. Keywords: application of the standard accounting education standards, technical competence, accounting programs, King Khalid University.